DESIGN AND CONSTRUCTION OF A MOBILE-BASED PLANT SEARCH APPLICATION IN THE QURAN WITH FUSE.JS IMPLEMENTATION - Fatiya Quzza; Kurnia Saputra; Zumaidar Zumaidar (BRIN - Badan Riset dan Inovasi Nasional, 2026)
The availability of applications that specifically integrate plant data in the Quran, related verses, and scientific information is still limited, as indicated by the absence of similar applications on platforms such as the Google Play Store and the App Store. Therefore, this study developed a mobile application supported by a web system for admin data management to provide information on plants in the Quran in a structured and easily accessible manner. The Rapid Application Development (RAD) method was applied for quick iteration and user testing. Data collection found 28 plants mentioned specifically and 11 generally in the Quran. The app displays plant information with related verses and scientific details. A search feature using Fuse.js was added for easier access. Usability testing with UMUX scored 91.53% (“best imaginable”), while black box testing shows the test scenario runs according to the expected results on both platforms.